What is (still) political about the city?. (January 2017) - Beveridge, Ross; Koch, Philippe
What happens to urban politics when examined through the post-political lens? In our response to Derickson, Dikec and Swyngedouw we reassert the key elements of our critique: the prescriptive understanding of politics and the inconsistent use of the urban. We close this debate with some thoughts on how we might urbanise the political.